Acute changes in lipoprotein subclasses during exercise - Søndergaard, Esben; Poulsen, Marianne K.; Jensen, Michael D.; Nielsen, Søren (Metabolism, clinical and experimental, 2014)
Lipids are important substrates for oxidation in the basal fasting state and during exercise. Studies have demonstrated beneficial changes in lipoprotein subclass composition the day after an exercise bout. However, the acute effect of exercise on TG concentration and lipoprotein subclass composition remains unclear. Sixteen lean, healthy individuals (8 men and 8 women) were recruited (age 20–30years, BMI<25kg/m2). The subjects were studied during basal fasting conditions as well as during and after 90min of cycling at 50% of VO2peak. Lipoprotein subclass composition was measured with 1H NMR spectroscopy. During exercise, LDL and HDL particle concentration increased significantly (p<0.05) despite lower total TG concentration. In addition, exercise resulted in a shift towards smaller VLDL particles in men (p<0.05), but VLDL–TG concentration was unaltered. Acute exercise induces beneficial changes in lipoprotein subclass composition. These changes are similar to the effects of exercise training.